THU0389 Is there any role of immunogenicity on the response to the anti-tumor necrosis factor alpha therapy in patients with ankylosing spondylitis: the first results of a prospective cohort study. (15th June 2017) - Akar, S; Cinar, M; Sargin, G; Karadag, O; Kinikli, G; Ozmen, M; Gercik, O; Kalyoncu, U; Yilmaz, S; Senturk, T; Keser, G; Hatemi, G; et al.
Abstract : Background: Although anti-tumour necrosis factor agents (anti-TNFs) are very effective in most patients with ankylosing spondylitis (AS) significant proportion of patients quit the treatment due to non-response or adverse events. The development of anti-drug antibodies (ADAs) and low serum drug levels might have a mechanistic role in loss of efficacy of or the development of adverse events in patients treated with anti-TNFs. There is limited data regarding the immunogenicity of anti-TNFs in patients with AS. Objectives: Therefore the aim of this study was to evaluatethe relationship between the formation of ADAs, serum through drug levels and clinical response to anti-TNFs in patients with AS. Methods: In total 350 AS patients with a new anti-TNF agent prescription in the last two weeks period were planned to include this multi-center prospective observational cohort study. Herein we are presenting the data of first 102 patients who had >3months follow-up. Clinical data and serum samples were collected at baseline and at every three months of treatment. Serum drug levels and ADAs were measured by ELISA in one center to avoid inter-assay variability. Results: 102 biologic naïve AS patients (75 [74%] male, mean (±SD) age; 37.2±10.7 years) who started anti-TNF agents (14 infliximab [13.7%], 27 adalimumab [26.5%], 33 etanercept [32.4%] and 28 golimumab [27.5%]) were included in the present analysis. In comparison to baseline values BASDAI, ASDAS-CRP and CRP values were significantly decreased in third months of follow-up ( P <0.001) (table). At 12 weeks of follow-up 9 patients (9%; 2 on infliximab and 7 adalimumab) had ADAs and 20 (20%; 10 on adalimumab, 4 infliximab, 4 golimumab and 2 etanercept) had no detectable drug levels.The presence of ADAs were significantly correlated with serum drug levels ( P <0.001). Up to 12 months of follow-up none of patients treated etanercept developed ADAs. Third month BASDAI and ASDAS-CRP values were significantly higher in patients with ADAs (BASDAI values were 5.2±1.4 vs 3.0±1.8; P <0.001 and ASDAS-CRP values were 3.1±1.0 vs 1.9±1.1; P <0.001) (figure) and patients with no detectable drug levels BASDAI values were 4.1±1.8 vs 2.9±1.8; P =0.012 and ASDAS-CRP values were 2.7±1.3 vs 1.9±1.0; P =0.015). Conclusions: ADAs against anti-TNF agents might develop as early as 12 weeks of treatment. Our results confirm that ADA development may hinder the anticipated response to anti-TNF agents in patients with AS. Disclosure of Interest: None declared